Proceso de producción temporal en la bananera orgánica leche y miel del Canton Jujan. - Sánchez Caicedo, José Ignacio (2022)
The present case study called "Temporary production process in the organic banana plant Milk and Honey of the Febres Cordero parish", aims to examine the agricultural production of organic bananas, in addition to verifying the difficulties that occur in the company, which Several methods and a series of information were used that helped to understand the drawbacks of said plantation. With the help of a descriptive research methodology together with technical instruments, it was possible to obtain excellent information, through surveys and interviews, carried out with the manager, administrator and agricultural workers of the Leche y Miel banana plantation, in which it was determined each of the shortcomings that were found in the company, in order to successfully conclude the document that uses a deductive method and help improve the production of said banana company, since they suffer from climatic difficulties that, in general, is unfavorable to the manager.